2014
DOI: 10.1007/s00134-014-3471-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival in solid cancer patients following intensive care unit admission

Abstract: Several factors have been associated with poor survival in ICU cancer patients; however, primary research is still needed to describe outcomes in cancer patients with sufficient case mix and treatment details to be of prognostic value to clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
84
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 59 publications
16
84
1
4
Order By: Relevance
“…In a systematic review of patients with solid tumors, 35 studies (25,339 patients) reported ICU and hospital mortality rates of 31.2 and 38.2 %, respectively [12]. These studies confirm the impact of performance status and mechanical ventilation on mortality, but also the lack of prognostic value of variables depicting the characteristics of the malignancy [13][14][15].…”
Section: Discussionmentioning
confidence: 83%
“…In a systematic review of patients with solid tumors, 35 studies (25,339 patients) reported ICU and hospital mortality rates of 31.2 and 38.2 %, respectively [12]. These studies confirm the impact of performance status and mechanical ventilation on mortality, but also the lack of prognostic value of variables depicting the characteristics of the malignancy [13][14][15].…”
Section: Discussionmentioning
confidence: 83%
“…It is likely that patients with cancer have yielded benefit from the technical progress in intensive care medicine in the same way as patients with other diseases. Conversely, admission to the ICU during an acute episode remains associated with a higher mortality rate than admissions arising from scheduled surgery (3,4,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported comparable ICU and hospital survival rates among critically ill patients with and without malignancy (1,2). This observation has led to a reappraisal of ICU admission policy for these patients.…”
mentioning
confidence: 97%
“…This is explained, at least in part, by the marked heterogeneity of the populations studied (1)(2)(3)(4)6,7). In a recent systematic review of 45 studies reporting on outcomes of critically ill patients with solid tumors, ICU mortality rates ranged from 4.5% to 85% (2).…”
mentioning
confidence: 99%